2018
DOI: 10.1101/334102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome-wide analysis of auxin-induced carotenoid accumulation in Chlorella microalgae

Abstract: Highlight: Transcriptomics of plant hormone-treated Chlorella revealed the active pathway components of auxin-induced carotenogenesis and included the ancient ABP1/SCF SKP2A /IBR5-mediated pathways. The manuscript presents the first documented transcriptomic data of auxin-treated microalgae. AbstractMicroalgae are a commercially viable route for the production of carotenoids, including β carotene and astaxanthin. In the current study, the commercially relevant microalga, Chlorella sp. BR2 was treated with four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…An increase in b* value can be related to the oil carotenoid content (Stoll et al, 2017). It was suggested that Zn promotes the tryptophan synthesis, an auxin precursor, which results in a higher level of auxin in plants, in turn inducing carotenoids biosynthesis pathway (Alsenani et al, 2018; Ljung, 2013). To the best of our knowledge, no data have been reported about the direct effect of Zn on L*, a*, and b* values of olive oil.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in b* value can be related to the oil carotenoid content (Stoll et al, 2017). It was suggested that Zn promotes the tryptophan synthesis, an auxin precursor, which results in a higher level of auxin in plants, in turn inducing carotenoids biosynthesis pathway (Alsenani et al, 2018; Ljung, 2013). To the best of our knowledge, no data have been reported about the direct effect of Zn on L*, a*, and b* values of olive oil.…”
Section: Resultsmentioning
confidence: 99%